Society for Endocrinology UK Guidance on the initial evaluation of a suspected difference or disorder of sex development (Revised 2021). (22nd June 2021) - Ahmed, S. Faisal; Achermann, John; Alderson, Julie; Crouch, Naomi S.; Elford, Sue; Hughes, Ieuan A.; Krone, Nils; McGowan, Ruth; Mushtaq, Talat; O'Toole, Stuart; Perry, Leslie; Rodie, Martina E.; et al.
Abstract: It is paramount that any child or adolescent with a suspected difference or disorder of sex development (DSD) is assessed by an experienced clinician with adequate knowledge about the range of conditions associated with DSD and is discussed with the regional DSD service. In most cases, the paediatric endocrinologist within this service acts as the first point of contact but involvement of the regional multidisciplinary service will also ensure prompt access to specialist psychology and nursing care. The underlying pathophysiology of DSD and the process of delineating this should be discussed with the parents and affected young person with all diagnostic tests undertaken in a timely fashion. Finally, for rare conditions such as these, it is imperative that clinical experience is shared through national and international clinical and research collaborations.